2003
DOI: 10.1109/tbme.2002.807327
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and measurement of flow effects on tracheal sounds

Abstract: The analysis of breathing sounds measured over the extrathoracic trachea offers a noninvasive technique to monitor obstructions of the respiratory tract. Essential to development of this technique is a quantitative understanding of how such tracheal sounds are related to the underlying tract anatomy, airflow, and disease-induced obstructions. In this study, the first dynamic acoustic model of the respiratory tract was developed that takes into consideration such factors as turbulent sound sources and varying g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…This clearly shows that the sound frequency distribution of a model strongly depends on airway geometry and that the level of the PSD depends on the air flow rate (which also determines the Reynolds number in the constricted region). These results are contradictory to the theory proposed by Hardin and Patterson (1979), but in agreement with observations of lung sound over a range of flow rates in the inspiratory maneuver (Gavriely and Cugell, 1996;Harper, et al, 2003). In some further studies, it was found that the characteristics of the inspiratory sound (mean, median, or the highest frequency) were changed when the patient performed a methacholine challenge test (Habukawa et al, 2010).…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…This clearly shows that the sound frequency distribution of a model strongly depends on airway geometry and that the level of the PSD depends on the air flow rate (which also determines the Reynolds number in the constricted region). These results are contradictory to the theory proposed by Hardin and Patterson (1979), but in agreement with observations of lung sound over a range of flow rates in the inspiratory maneuver (Gavriely and Cugell, 1996;Harper, et al, 2003). In some further studies, it was found that the characteristics of the inspiratory sound (mean, median, or the highest frequency) were changed when the patient performed a methacholine challenge test (Habukawa et al, 2010).…”
Section: Discussionsupporting
confidence: 41%
“…In the higher constriction level model, compressibility of the flow must also be considered and this may lead to a significant increase in the higher frequency range. Physically, high frequency sound might be reduced during lung sound measurement from the chest surface because lung parenchyma acts as a low-pass filter, with a general threshold frequency of 1000 Hz (Schreur et al, 1995), or 2000 Hz (Harper et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, body sound recorded at the trachea is affected by individual anatomy. 22 To compensate for this variation, the correlation between sound amplitude and airflow is individually and continuously recalculated.…”
Section: Automated Apnea and Hypopnea Detectionmentioning
confidence: 99%
“…Breath sounds have a strong relationship with flow rate [20][21][22][23] . That is, all frequency components of spectral power are changed with flow rate: the higher the flow rate, the higher the spectral power.…”
Section: Th +mentioning
confidence: 99%